2014
DOI: 10.1021/la502559r
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Nonionic Dodecanol Ethoxylates at the Oil–Water Interface: Effect of Increasing Head Group Size

Abstract: The conformation of charged surfactants at the oil-water interface was recently reported. With the aim to assess the role of the head group size on the conformation of the adsorbed layer, we have extended these studies to a series of nonionic dodecanol ethoxylate surfactants (C12En, ethylene oxide units n from 6 to 12). The study was performed using neutron reflectometry to enable maximum sensitivity to buried interfaces. Similarly to charged surfactants, the interface was found to be broader and rougher compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…While the textbooks and review articles also show the surfactants and co-surfactants forming a monolayer at the surfaces of the oil droplets in a cream, we show here that this interfacial layer is very diffuse, suggesting that it is significantly roughened, with the constituent molecules not aligned but staggered. Again, this is entirely consistent with the observations made by Zarbakhsh et al 22,39,40,42,43 wherein the surfactant and lipid layers that form at oil-water interfaces are shown to exhibit a pronounced roughening which cannot be explained simply by thermal broadening and is considered to arise instead because of a staggering of the molecules' hydrocarbon chains brought about by their dissolution within the oil and the resultant disruption of their side-by-side packing.…”
Section: Discussionsupporting
confidence: 90%
“…While the textbooks and review articles also show the surfactants and co-surfactants forming a monolayer at the surfaces of the oil droplets in a cream, we show here that this interfacial layer is very diffuse, suggesting that it is significantly roughened, with the constituent molecules not aligned but staggered. Again, this is entirely consistent with the observations made by Zarbakhsh et al 22,39,40,42,43 wherein the surfactant and lipid layers that form at oil-water interfaces are shown to exhibit a pronounced roughening which cannot be explained simply by thermal broadening and is considered to arise instead because of a staggering of the molecules' hydrocarbon chains brought about by their dissolution within the oil and the resultant disruption of their side-by-side packing.…”
Section: Discussionsupporting
confidence: 90%
“…However, maintaining a constant oil film thickness was a challenging task, and the methodology was applicable only to volatile oils. In recent years, an alternative methodology has been developed to control the oil via film coating, allowing more systematic studies of surfactant adsorption at the oil/water interface. To avoid drastic attenuation of the neutron beam upon traversing the oil phase, a thin oil (hexadecane) layer is coated and then sandwiched between a silicon substrate and the aqueous phase. However, reflectivity from the silicon/oil interface interferes with that from the oil/water interface and must thus be minimized by matching the scattering length density (SLD or Nb ) of the oil to that of silicon.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study indicated that mAbs and nonionic surfactants might co-adsorb at the oil/water interface. 17 It is useful to understand how mAbs and surfactants adsorb alone 18 and as a mixture at the silicone oil/water interface and how the interfacial adsorption processes impact the structure of the adsorbed mAb molecules. This insight could help optimize formulation design and/or surface treatments.…”
Section: Introductionmentioning
confidence: 99%